2013
DOI: 10.1190/tle32111374.1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of 3D tilted resistivity anisotropy on marine CSEM measurements

Abstract: O f f s h o r e a n d o n s h o r e b r o a d b a n d s e i s m o l o g y 1374 The Leading Edge November 2013 SPECIAL SECTION: Offshore and onshore broadband seismologyThe impact of 3D tilted resistivity anisotropy on marine CSEM measurements M arine CSEM modeling and data-interpretation algorithms currently used by the E&P industry are based on application of vertical transverse isotropic (VTI) resistivity models, which in many practical cases cannot adequately describe complex tilted anisotropic geologic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 21 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…This VTI assumption is suitable for sedimentary rock formations with approximately horizontal bedding. For dipping formations, however, the additional effect of the tilted transversely isotropic (TTI) formation can have a significant impact on marine CSEM data, as shown by Davydycheva and Frenkel (2013). In this paper, we show how TTI anisotropy can be included in a 3D inversion of marine CSEM data and compare VTI and TTI imaging results for a synthetic model and a CSEM field data set acquired over steeply dipping geology.…”
Section: Introductionmentioning
confidence: 97%
“…This VTI assumption is suitable for sedimentary rock formations with approximately horizontal bedding. For dipping formations, however, the additional effect of the tilted transversely isotropic (TTI) formation can have a significant impact on marine CSEM data, as shown by Davydycheva and Frenkel (2013). In this paper, we show how TTI anisotropy can be included in a 3D inversion of marine CSEM data and compare VTI and TTI imaging results for a synthetic model and a CSEM field data set acquired over steeply dipping geology.…”
Section: Introductionmentioning
confidence: 97%
“…This assumption works well provided that the anisotropic formations do not have significant dip. However, recent modeling studies (Davydycheva and Frenkel, 2013;Li and Dai, 2011) have shown that the effect of dipping anisotropy, known as tilted transverse isotropy (TTI), can have a significant impact on marine CSEM data, and cannot be accurately modeled under the VTI assumption. A pertinent question is therefore what effect TTI has on VTI inversion, and how to properly account for TTI in inversion.…”
Section: Introductionmentioning
confidence: 99%